Female migrant workers, family welfare, and Islamic economic philosophy: A gender-based empirical study in Indonesia - Ceasar, Ibnul Jauzi Abdul; Yusdani, Yusdani; Mu’allim , Amir (Universitas Islam Indonesia, 2025)
IntroductionFemale labor migration has become an increasingly important livelihood strategy for households in migrant-sending regions, particularly in developing and Muslim-majority contexts. In Indonesia, women’s migration is closely linked to family survival, remittance dependence, and changing gender relations. While existing studies widely acknowledge the economic contribution of female migrant workers, fewer have examined family welfare through an integrated framework that combines gender analysis with Islamic economic philosophy. As a result, ethical, social, and religious dimensions of welfare remain underexplored in migration scholarship.ObjectivesThis study aims to analyze the role of female migrant workers in improving family welfare by integrating Islamic economic philosophy and gender perspectives. Specifically, it seeks to examine changes in household welfare, gender relations, consumption behavior, and religious-ethical practices among migrant families, as well as to assess how these dimensions interact in shaping overall family well-being.MethodThe study employed a qualitative field research design conducted in the Special Region of Yogyakarta, Indonesia. Data were collected from 34 informants, including female migrant workers, former migrant workers, and family members, through in-depth interviews, observation, and documentation. An inductive analytical approach was applied using the trilogy of Islamic economic philosophy—anthropological, cosmological, and theological dimensions—to interpret empirical findings. Data analysis followed systematic stages of reduction, display, and verification to ensure credibility and rigor.ResultsThe findings show that female labor migration contributes significantly to household welfare by improving basic and intermediate living conditions, particularly food security, housing, education, and healthcare. However, welfare gains tend to remain limited and do not consistently lead to long-term economic sustainability. Women’s roles as primary income earners enhance their bargaining power within households, although relational tensions persist due to entrenched gender norms. Increased income often alters consumption patterns, sometimes generating ethical tensions with Islamic principles of moderation, while religious commitment plays a key role in fostering moral resilience and family cohesion.ImplicationsThe study highlights the need for migration policies and support programs that integrate economic empowerment with ethical guidance, financial literacy, and family-centered interventions. It also underscores the importance of incorporating spiritual and gender-sensitive dimensions into welfare assessment and migrant protection frameworks.Originality/NoveltyThis research contributes to migration and welfare studies by empirically operationalizing Islamic economic philosophy alongside gender analysis. It offers a multidimensional understanding of family welfare that moves beyond material indicators and enriches scholarly debates on female labor migration in Muslim-majority contexts.